KINERJA KARYAWAN PT. BPR BKK JATENG (PERSERODA) KANTOR CABANG KARANGANYAR - Giyono, Giyono; Kamulat, Kunti Fitri (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The research’s aim to determine the effect of the work environment, compensation and work discipline on employees’s performance of PT. BPR BKK Jateng (Perseroda) Karanganyar Branch Office both partially and simultaneously. This is a quantitative research using primary data by questionnaires distributed to respondents, with 100 data obtained. Data analysis used in this research is descriptive analysis, multiple linear regression test, t test, F test and coefficient of determination test. The research’s results shows that the work environment, compensation and work discipline affect the employees’s performance at PT. BPR BKK Jateng (Perseroda) Karanganyar Branch Office both partially and simultaneously.